Penal Law and Penal Precept as sources of ecclesiastical penalty - Saj, Marek (Prawo Kanoniczne, 2024)
This publication was intended to show the Penal Law and the Penal Precept as sources of ecclesiastical penalty. This issue covers eight canons (1313-1320) of the Code of Canon Law. In addition to their analysis, an amendment by Pope Francis in 2021 and their new Polish translation are highlighted.